Pengenalan Sains bagi Anak Oleh Orang Tua di Lingkungan Keluarga - Anggraeni Mashinta Sulistyani (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Purwokerto, 2016)
Abstract: family is the first environment known to the children in foster their potential. Families will contribute to the formation personality, intellectual and spiritual intelligence. Education by parents or family is an early foundation for children. It most contextual sometimes not realized the parents is to introduce science to children. Science is often considered as hard to be understood, it is because the parents did not introduce science to children from an early age. Introducing science to children can be fun method and with a simple object of study, involving objects around the child as water, air, fire, earth, plants, animals, sound, and himself. Through science, children can be perform simple experiments. The trail train children to link cause and effect of a treatment that trains children to think logically and be able to solve the problem. Studying science is also beneficial to increase the creativity of children, improve cognitive, and train children to think criticaly. Threfore, introducing and training science or early childhood is a very important thing. Keywords: Introduction to Science, Children, Parents, Family Environment.